2013
DOI: 10.1165/rcmb.2012-0103oc
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-Activated K+ Channel–3.1 Blocker TRAM-34 Attenuates Airway Remodeling and Eosinophilia in a Murine Asthma Model

Abstract: Key features of asthma include bronchial hyperresponsiveness (BHR), eosinophilic airway inflammation, and bronchial remodeling, characterized by subepithelial collagen deposition, airway fibrosis, and increased bronchial smooth muscle (BSM) mass. The calcium-activated K(+) channel K(Ca)3.1 is expressed by many cells implicated in the pathogenesis of asthma, and is involved in both inflammatory and remodeling responses in a number of tissues. The specific K(Ca)3.1 blocker 5-[(2-chlorophenyl)(diphenyl)methyl]-1H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 50 publications
(62 reference statements)
0
26
0
Order By: Relevance
“…Another question is of course whether KCa3.1 inhibition, which we and others have previously proposed for the treatment of asthma, 34 inflammatory bowel disease 35 and transplant vasculopathy 22 will increase the risk of infections. In this context, it should be kept in mind that the interactions between the brain and the immune system during and after stroke are complex.…”
Section: Discussionmentioning
confidence: 99%
“…Another question is of course whether KCa3.1 inhibition, which we and others have previously proposed for the treatment of asthma, 34 inflammatory bowel disease 35 and transplant vasculopathy 22 will increase the risk of infections. In this context, it should be kept in mind that the interactions between the brain and the immune system during and after stroke are complex.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting K Ca 3.1 genetically or pharmacologically reduces FcɛRI-mediated Ca 2+ influx and degranulation (344). Moreover, KCa3.1 − / − mice showed reduced passive cutaneous and systemic anaphylaxis (344), and K Ca 3.1 inhibitors attenuated airway remodeling and eosinophilia in murine and sheep asthma models (345, 346). However, while inhibition of mast cell function probably contributed to these effects, K Ca 3.1 is also expressed in T cells, fibroblasts, and proliferative airway smooth muscle cells.…”
Section: Ion Channels In Mast Cells and Allergymentioning
confidence: 99%
“…The K Ca 3.1 knockout mouse displays an attenuated IgE-dependent systemic anaphylactic response. In a mouse model of asthma, treatment with the specific K Ca 3.1 blocker TRAM-34 attenuated OVA-dependent bronchial hyperresponsiveness, bronchoalveolar lavage eosinophilia, sub-basement membrane collagen deposition, airway smooth muscle mass and peribronchiolar fibrosis 3. Another mouse study demonstrated a role for K Ca 3.1 channels in the development of obliterative bronchiolitis following transplantation.…”
Section: Kca31mentioning
confidence: 97%